Factorise :(x+6)•(x+2)=0[This is a quadratic equation]
2 answers:
- (x+6)(x+2)=0
- x(x+2)+6(x+2)=0
- x²+2x+6x+12=0
- x²+8x+12=0
The zeros are
Answer:
<u>x = -6</u>
<u>x = -2</u>
Step-by-step explanation:
Finding the zeros :
By this, we understand that if either of the factors equals 0, then the expression's value will also be 0.
- x + 6 = 0 ⇒ <u>x = -6</u>
- x + 2 = 0 ⇒ <u>x = -2</u>
<u />
Solution :
- <u>x = -6</u>
- <u>x = -2</u>
You might be interested in
Answer: 35.2101
( Hope your day goes well :) )
Step-by-step explanation:
-1,6 is -1 left 6 up
1,-6 is 1 right -6 down
6,-1 is 6 right -1 down
Answer:
3x^2 -7x +2
Step-by-step explanation:
(15x^2 -35x+10) ÷5
(15/5x^2 -35/5x+10/5)
3x^2 -7x +2
This will factor
(3x-1) (x-2)
Answer:
The integer is -16
Step-by-step explanation:
The first scuba diver is 23 feet below sea level. THe second is 7 feet closer.
23 - 7 = 16. He is still under sea level, so it would be -16
X+ y = 10
2x = 2y+4
2x/2 = 2/2y+4/2
x = y + 2
x+y = 10
y+2+y=10
2y + 2 = 10
2y +2-2 =10-2
2y = 8
2y/2 =8/2
y = 4
x + y =10
x + 4 =10
x +4-4 =10-4
x = 6
Check
2x = 2y +4
2(6) = 2(4) +4
12 = 8+4
12= 12